Diagnostic Study of Open-Wells in Jabalpur - K, Hardaha M; K, Nema R (Journal of Agricultural Engineering, 2005)
In Narmada valley small farms depend upon large diameter openwells for irrigation. Openwells also meet the domestic water requirements of large rural population. There are sixty-five open wells in and around Jawaharlal Nehru Krishi Vishwa Vidyalaya, Jabalpur. A diagnostic study was carried out to find out sick openwells, causes of their sickness and possibilities to increase yield. Diameter of openwells studied varied from 1,30 m to 6.22 m and their depth varied from 2.10 m to 15.50 m. It was found that more than 60 percent openwells are sick due to one or other reasons. Sickwells have been grouped into five categories based on the cause of sickness. Each cause has been discussed. Fourteen out of 40 sickwells are yielding low due to lowering of water table ,below the well bottom, whereas 11 wells are sick due to deposition of debris. In order to rejuvenate wells that are sick due to insufficient depth for interception of upper aquifer, necessary depth of digging has been worked out. Depth of aquifer has been determined with the help of three-dimensional panel diagram prepared using well-logs of existing tubewells. Some of the sickwells have been rejuvenated to verify the recommendation made. Changes in the yield of the rejuvenated openwells have been analyzed by recuperation test of the well.